A Memory of My Teacher Professor Kosta Dimitrov Pergelov - Oreshkova, Hristina (Research Papers, 2023)
The article is dedicated to the 100th anniversary of the birth of the prominent Bulgarian scientist economist and accountant Kosta Dimitrov Pergelov. The author expresses deep gratitude and appreciation to the Honourable Professor Kosta Dimitrov Pergelov – Doyen of accounting science and practice, of accounting education and postgraduate education and qualification in Bulgaria.The article is an expression of the author’s admiration and deep esteem for the highly humane and noble work and rich scientific creativity of Professor Kosta Dimitrov Pergelov. The article highlights essential features of the Professor’s intellectual and spiritual image, his vivid and fascinating personality, moral and ethical advancement and erudition. The author reveals the favourable and fruitful influence of Professor Kosta Pergelov as a scientist, academician, pedagogue and educator on generations of students, young researchers, scholars, and lecturers. The Professor’s enormous contribution to accounting as science and practice, to accounting education and establishment of the postgraduate education system in Bulgaria and its functioning, is also highlighted and emphasized.The author recreates her memories from her long-term collaboration with Professor Kosta Pergelov and relies on works created by the Professor, which have turned into emblematic milestones for contemporary Bulgarian accounting science, and into a substantial part of its golden fund.
Keywords: Accounting education; Kosta Pergelov; Charismatic personality; Accounting science; Accounting practice